Schola Prophetarum: Prophetic Preaching Toward a Public, Prophetic Church (Homiletic, 2009)
Prophetic preaching has for much of the last century been dominated by a classically liberal, Lone Ranger view of Hebrew Bible prophecy that is both a distortion of the past and increasingly problematic in the present. In this article, the author reconsiders the social shape of Hebrew Bible prophecy and joins to it the unusual contours of New Testament prophecy and its accompanying ecclesial practice of "discernment." These become resources for rethinking prophetic preaching theologically as an ecclesial task for a disestablished church desiring to move beyond post-liberal "resident alien" models and embracing prophetic preaching as a public form of shared ecclesial engagement for the sake of the world God so loves. In doing so, he seeks to connect with models of prophetic preaching as a shared, public task articulated most recently by scholars such as McClure, Andrews, Ottoni Wilhelm, and Ramsey.